Long-term follow up of fecundability after ectopic pregnancy in Taiwan: a nationwide population-based study - Yin, Chih-Hsiang; Lee, Yi-Liang; Chang, Chia-Ching; Chien, Wu-Chien; Wu, Gwo-Jang (Frontiers in Medicine, 2024)
Background: Ectopic pregnancy (EP) occurs when a fertilized ovum is implanted outside the uterine cavity. Its incidence is 2% of all pregnancies and is known to decrease fertility. This study aimed to measure pregnancy rates after EP, identify the various parameters influencing pregnancy, and compare these variables in women with and without a history of EP, as well as determine in which medical facilities women with EP seek medical help. Methods: The data was extracted from the National Health Insurance Research Database during 2000–2013. The study group included of women with a history of one EP (study group) and women without EP (control group). The chi-square/Fisher exact test was performed for categorical variables, and t-tests were used for continuous variables. Results: The EP group had a higher cumulative pregnancy rate (41.55%) than the control group (37.14 %), and a 1.16 times higher rate in developing pregnancy (p<0.001). While the pregnancy rate in the EP group was initially lower than in the control group during the first 5 years, it surpassed the control group’s rate between the 10th and 14th years. Conclusions: Fecundability after EP was lower at the beginning but increased at long-term follow-up.